2022
DOI: 10.2991/assehr.k.220108.036
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning System in Civic Education Courses to Develop Humanity Literacy

Abstract: Humanity literacy is the end of data and technology literacy because 21 st century learners are human resources who are literate with data and technology and can use them for a nobler life. Civic Education has a central role in building the quality of education in Indonesia, especially the development of human literacy. However, so far, it has experienced obstacles in the implementation process. Blended Learning is one of the best systems for Learning, from transition classes to e-learning. This method is very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, a previous study revealed that the use of applications as learning media can increase data literacy, technology literacy, and human literacy [28]. Kusnadi et al [29] in their literature review also mentioned that lesson plans which integrate multiple approaches, models of teaching, and methods of teaching, as well as the utilization of various media, will make human literacy more successful. This is as done by Hartanto et al [30] who developed a digital module (flipbook) for human literacy.…”
Section: Do the Models Of Teaching Strengthen Students' Human Literacy?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study revealed that the use of applications as learning media can increase data literacy, technology literacy, and human literacy [28]. Kusnadi et al [29] in their literature review also mentioned that lesson plans which integrate multiple approaches, models of teaching, and methods of teaching, as well as the utilization of various media, will make human literacy more successful. This is as done by Hartanto et al [30] who developed a digital module (flipbook) for human literacy.…”
Section: Do the Models Of Teaching Strengthen Students' Human Literacy?mentioning
confidence: 99%
“…As mentioned by Jalinus et al [33], the blended learning can be applied in vocational education with a focus on the components of the Industry 4.0, including human literacy. Likewise, Kusnadi et al [29] found that blended learning works well for getting students to interact and learn content outside the classroom. In addition, they believed that this model affects students' ability to develop human literacy in the use of data and technology.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%